Identification of MicroRNAs as Potential Biomarker for Gastric Cancer by System Biological Analysis. (28th May 2014) - Yan, Wenying; Wang, Shouli; Sun, Zhandong; Lin, Yuxin; Sun, Shengwei; Chen, Jiajia; Chen, Weichang
Abstract : Gastric cancers (GC) have the high morbidity and mortality rates worldwide and there is a need to identify sufficiently sensitive biomarkers for GC. MicroRNAs (miRNAs) could be promising potential biomarkers for GC diagnosis. We employed a systematic and integrative bioinformatics framework to identify GC-related microRNAs from the public microRNA and mRNA expression dataset generated by RNA-seq technology. The performance of the 17 candidate miRNAs was evaluated by hierarchal clustering, ROC analysis, and literature mining. Fourteen have been found to be associated with GC and three microRNAs (miR-211, let-7b, and miR-708) were for the first time reported to associate with GC and may be used for diagnostic biomarkers for GC.